Development and performance evaluation of an intelligent air purifier/humidifier using fuzzy logic controller - Emenuvwe, Omonigho Peter; Umar, Umar Ali; Umaru, Samaila; Oyedeji, Ayodeji Nathaniel (International journal of low carbon technologies, 2023)
Abstract This study aimed to develop and implement a fuzzy logic controlled-intelligent air purifier/humidifier. The concepts of passive purification and evaporative humidification were used to build this device, and engineering ideas and theories were used to guide the development of electrical and mechanical systems. Additionally, a fuzzy logic controller was designed, built and integrated into the air purifier/humidifier device to help with its operation. It does this by analysing input signals from all the sensors (dust, volatile organic compound gas, humidity and water level) and activating the actuators (suction and blow fan). On the Arduino IDE, a C/C++ programming code was developed and uploaded onto the Arduino Uno R3 board, which houses the ATmega328P microcontroller processor. In estimating the clean air delivery rate (CADR), noise level and moisture delivery rate, the performance of the developed air purifier/humidifier was assessed. Additionally, the electrical systems’ power consumption and the fuzzy logic controller’s ease of use were each assessed. In light of the room capacity taken into consideration, the findings obtained demonstrated that the proposed air purifier/humidifier device satisfies the minimum standard requirement of a CADR of 140m3/hr. The outcome also revealed that the designed device’s noise level is lower than the typical threshold for an air purifier, which is less than 40 db. Additionally, after 68 minutes, the device raised the humidity level in a controlled area from 21% to 40%.